PARP inhibition impedes the maturation of nascent DNA strands during DNA replication - Vaitsiankova, Alina; Burdova, Kamila; Sobol, Margarita; Gautam, Amit; Benada, Oldrich; Hanzlikova, Hana; Caldecott, Keith W (Nature structural & molecular biology, 2022)
Poly(ADP-ribose) polymerase 1 (PARP1) is implicated in the detection and processing of unligated Okazaki fragments and other DNA replication intermediates, highlighting such structures as potential sources of genome breakage induced by PARP inhibition. Here, we show that PARP1 activity is greatly elevated in chicken and human S phase cells in which FEN1 nuclease is genetically deleted and is highest behind DNA replication forks. PARP inhibitor reduces the integrity of nascent DNA strands in both wild-type chicken and human cells during DNA replication, and does so in FEN1-/- cells to an even greater extent that can be detected as postreplicative single-strand nicks or gaps. Collectively, these data show that PARP inhibitors impede the maturation of nascent DNA strands during DNA replication, and implicate unligated Okazaki fragments and other nascent strand discontinuities in the cytotoxicity of these compounds.
Keywords: replikace DNA; poškození DNA; DNA Damage; Poly(ADP-ribose) Polymerase Inhibitors; PARP inhibitory; DNA Repair; oprava DNA; Poly (ADP-Ribose) Polymerase-1; DNA; poly(ADP-ribosa)polymerasa 1; DNA Replication